Steady-state dynamic method: An efficient and effective way to predict dynamic modulus of asphalt concrete. (15th May 2016) - Cao, Peng; Jin, Feng; Zhou, Changjun; Feng, Decheng; Song, Wenchao
Highlights: Transient and steady-state dynamic methods were used to obtain asphalt concrete E ∗ . The steady-state dynamic method is more efficient in calculating asphalt concrete E ∗ . The steady-state dynamic method is proved effective to predict asphalt concrete E ∗ . Abstract: This study presents two meso-mechanical methods of analyzing the asphalt concrete's dynamic modulus, including the transient dynamic method (implicit dynamic method) based on the modified Newmark numerical differential algorithm and the steady-state dynamic method based on the perturbation theory. The results indicate that compared to the transient dynamic method based on the modified Newmark numerical differential algorithm, the steady-state dynamic method based on the perturbation theory is much more efficient in calculating dynamic modulus of asphalt concrete while maintaining similar accuracy. Furthermore, the random aggregate model of asphalt concrete coupled with the steady-state dynamic method is also employed to obtain the asphalt concrete's dynamic modulus. The numerical solution was found in a good agreement with the corresponding experiment results, which indicates the proposed steady-state dynamic method an efficient and effective way to predict the dynamic modulus of asphalt concrete.